Khaleeji Modernities: Private Spaces, British Imperialism, and the Centralization of the Qatari Peninsula - Javier Guirado Alonso (15445457) (2023)
The majlis was a key political and social mechanism that defined the social and political structure of Qatar during the late nineteenth and early twentieth centuries, an epoch of transformation in the Indian Ocean world. The new policy of the British empire throughout the Indian Ocean during the late nineteenth and early twentieth centuries led to an increased centralization of the forms of authority that were present on its shores. This centralization shaped the institutional blueprint of Qatar, and not the discovery and exploitation of oil in the mid-twentieth century, which instead, took place successfully thanks to these institutional innovations. The majlis is a space and informal institution present in many Arab countries, and particularly relevant in the Gulf, in which members of a family and other notables gather and discuss a wide range of topics on a regular basis. Many studies have highlighted the importance of the majlis in the Gulf, yet its relation to the British colonial system remains largely underexplored. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_34